AEROTENK-BIOLOGICAL METHOD FACILITY FOR WASTEWATER TREATMENT - Iskandarova G.T.; Yusupkhujaeva A.M. (Web of Journals Publishing, 2023)
Biological purification uses the vital activity of microorganisms in the soil. These microorganisms cause the oxidation (rotting) of organic substances in the waste liquid, due to which their mineralization and natural neutralization of bacteria occur. The waste liquid during biological treatment is almost completely freed from organic substances and bacteria. Oxygen, necessary for the vital activity of microorganisms, comes from the air, in addition, compressors are supplied to the aerotank.
Keywords: aerotank, biological treatment, activated sludge, waste water, organic substances.